In vitro degradation and total gas production of byproducts generated in the biodiesel production chain (Acta Scientiarum. Animal Sciences, 2015)
This study aimed to evaluate the in vitro degradation and total gas production of different oil seed press cakes from a biodiesel production chain gas through the use of a semi-automatic technique of gas production in vitro. The treatments consisted of substituting elephant grass in increasing levels, 0%, 30, 50 and 70%, with the byproducts of Gossyypium hirsutum, Ricinus communis, Moringa oleifeira, Jatropha curcas and Helianthus annus. The oil seed press cakes of Moringa oleifeira had the highest rate of in vitro degradation of dry matter compared with other foods but did not result in a higher final volume of gases production. Gossyypium hirsutum, Pinhão manso curcas and Ricinus communis showed a higher in vitro degradability of similar dry matter. The highest total gas production was obtained by the oil seed press cakes of Helianthus annus. The oil seed press cakes of Moringa oleifeira can replace elephant grass up to 70% and therefore reduce both greenhouse gas emissions and energy loss for the animal.